Early or delayed enteral feeding for preterm growth-restricted infants: a randomized trial. - Leaf, A; Dorling, J; Kempley, S; McCormick, K; Mannix, P; Linsell, L; Juszczak, E; Brocklehurst, P (2012)
BACKGROUND: Growth-restricted preterm infants are at increased risk of developing necrotizing enterocolitis (NEC) and initiation of enteral feeding is frequently delayed. There is no evidence that this delay is beneficial and it might further compromise nutrition and growth. METHODS: Infants with gestation below 35 weeks, birth weight below the 10th centile, and abnormal antenatal umbilical artery Doppler waveforms were randomly allocated to commence enteral feeds "early," on day 2 after birth, or "late," on day 6. Gradual increase in feeds was guided by a "feeding prescription" with rate of increase the same for both groups. Primary outcomes were time to achieve full enteral feeding sustained for 72 hours and NEC. RESULTS: Four hundred four infants were randomly assigned from 54 hospitals in the United Kingdom and Ireland (202 to each group). Median gestation was 31 weeks. Full, sustained, enteral feeding was achieved at an earlier age in the early group: median age was 18 days compared with 21 days (hazard ratio: 1.36 [95% confidence interval: 1.11-1.67]). There was no evidence of a difference in the incidence of NEC: 18% in the early group and 15% in the late group (relative risk: 1.2 [95% confidence interval: 0.77-1.87]). Early feeding resulted in shorter duration of parenteral nutrition and high-dependency care, lower incidence of cholestatic jaundice, and improved SD score for weight at discharge. CONCLUSIONS: Early introduction of enteral feeds in growth-restricted preterm infants results in earlier achievement of full enteral feeding and does not appear to increase the risk of NEC.